Neutrophil depletion enhanced the Clostridium novyi-NT therapy in mouse and rabbit tumor models. Issue 1 (21st December 2021) - Staedtke, Verena; Gray-Bethke, Tyler; Liu, Guanshu; Liapi, Eleni; Riggins, Gregory J; Bai, Ren-Yuan
Abstract: Background: Hypoxia is a prominent feature of solid tumors and can function as fertile environment for oncolytic anaerobic bacteria such as Clostridium novyi -NT ( C. novyi -NT) where it can induce tumor destruction in mice and patients. However, two major obstacles have limited its use, namely the host inflammatory response and the incomplete clearance of normoxic tumor areas. Methods: In this study, we first used a subcutaneous tumor model of a glioblastoma (GBM) cell line in immunocompetent mice to investigate the local distribution of tumor hypoxia, kinetics of C. novyi -NT germination and spread, and the local host immune response. We subsequently applied the acquired knowledge to develop a C. novyi -NT therapy in an orthotopic rabbit brain tumor model. Results: We found that local accumulation of granular leukocytes, mainly neutrophils, could impede the spread of bacteria through the tumor and prevent complete oncolysis. Depletion of neutrophils via anti-Ly6G antibody or bone marrow suppression using hydroxyurea significantly improved tumor clearance. We then applied this approach to rabbits implanted with an aggressive intracranial brain tumor and achieved long-term survival in majority of the animals without apparent toxicity. Conclusion: These results indicated that depleting neutrophils can greatly enhance the safety and efficacy of C. novyi -NT cancer therapy for brain tumors.